Explosives initiation mechanism by high – current electron beam pulse. Overview - Plotnikov, S.V.; Turlybekuly, A.; Manapbaeva, A.B. (Recent Contributions to Physics, 2017)
The research urgency of the explosives initiation mechanism by a high-current pulsed electron beam is due to general scientific and practical interest in the study of fundamental phenomena in the interaction of powerful directed energy flows with condensed media. In particular, it has a great practical importance to study the process of electron-beam initiation of energy materials in order to use this method of detonation for technological purposes (coating, explosion welding, etc.). It is known that the action of a high-current electron beam on dielectrics and semiconductors leads to a change in the optical, electrical, and mechanical properties of materials. The article presents the main points of the initiation mechanism of explosives by high-current electron beam. Providence overview of scientific papers devoted to the study of nature initiating explosive mechanism under the influence of high-current electron beam. It is shown that on the verge of initiating an explosion glow of energetic materials is determined by two physical processes - pulsed solid cathodoluminescence, which occurs only when the pulse irradiation and glow of explosive decomposition products (plasma), which is formed after the induction period. The applied methods previously recording the spectra of the explosion of energetic materials have insufficient spectral resolution, which did not allow to identify the products of explosive decomposition studied explosives.
Keywords: high-current electron beam initiation mechanism explosives